HEMATOLOGICAL PARAMETERS OF THE BLOOD OF CATTLE DISEASED WITH TRICHUROSIS UNDER DIFFERENT TREATMENT SCHEMES - Shevchenko, T. S. (Scientific Progress & Innovations, 2019)
Trichurosis belongs to a widespread animal helminthiasis. This disease in cattle is caused by two species of nematodes of Trichuris: T. ovis and T. skrjabini genus, which parasitize, mainly in the blind gut and the colon. Trichuryses penetrating into the intestinal mucosa cause inflammation, edema, and irreversible changes in the places of infestation. At a high degree of invasion, trichurosis is clinically manifested in the form of diarrhea, exhaustion, intoxication, and death. The article presents the results of studies on changes in hematological parameters of heifer’s blood suffering from trichurosis after administering preparations according to different treatment schemes. For conducting the experiment on the private farm “RVD-Agro”, 5 groups of heifers 6−18 months of age were formed, which were prescribed Promectin 1 % and Albentabs 360 preparations according to different schemes. The blood was taken before giving the medicines, on the 5th and 10th day after the last administration of the preparations. Prior to conducting the research a reduced number of erythrocytes, hemoglobin and hematocrit content was recorded in heifers of all experimental groups, which was a sign of anemia. According to the study results it was established that the injection prep-aration Promectin 1 % was effective enough for both single and double administration. On the 10th day after injecting the last dose of the preparation, the number of erythrocytes in the animals increased to the level of physiological limits, and the content of hemoglobin increased by 15 % at single preparation administration and by 6 % at using Promectin for 2 days. Albentabs 360 proved to be effective only at double using. Name-ly, on the 10th day after the last preparation administration, the number of erythrocytes increased by 11 %, reaching the level of physiological limits, hemoglobin content increased by 7 % in the experimental animals and at the end of the treatment the indices remained outside the physiological norm. At single administering, Albentabs 360 turned out to be ineffective: the number of erythrocytes had decreased by the end of the exper-iment by 8 %, and hemoglobin content − by 7 %, as compared with the corresponding indices before the treatment.